The Effect of Role Conflict and Transformational Leadership on Organizational Commitment with Job Satisfaction as a Mediation Variable on Members of the Regional Coordination Team in West Sumatra Province - Aulia Putra Kapur; Harif Amali Rivai; Laura Syahrul (Journal of Social Research, 2023)
This study aims to determine and analyze the effect of role conflict and transformational leadership on organizational commitment with job satisfaction as a mediating variable in regional cooperation team members in West Sumatra Province. in the success of the Team's performance in carrying out tasks that are influenced by the job satisfaction provided by the team. The sampling technique was carried out using simple random sampling method with a total sample of 105 members. This study uses Partial Least Squares-Structural Equations Modeling (PLS-SEM) with the smartPLS 3 program. The results show that transformational leadership has a positive and significant effect on job satisfaction while transformational leadership has no positive and significant effect on organizational commitment, then job satisfaction has no effect negative and not significant to organizational commitment then role conflict has no positive and not significant effect on job satisfaction then role conflict has no negative and not significant effect on organizational commitment and job satisfaction does not mediate the relationship between transformational leadership on organizational commitment and job satisfaction does not mediate role conflict towards organizational commitment. then the implication of this research is to evaluate work processes and leadership styles so as to reduce the occurrence of role conflicts with employees. This can be done by reducing the demands of job roles that exceed the resources of the employee. In addition, establishing better communication between employees and with superiors can also minimize the occurrence of role conflicts and it is hoped that leaders can improve ways of leading in order to increase employee satisfaction and performance because the benchmark for the success of an institution is joint success due to the satisfaction and performance of its employees. very good.